Ask Only What Your Country Can Do for You: Group Interests, Constituency Characteristics and Demands for Representation. Issue 1 (January 2021) - Christenson, Dino P.; Lin, Jennifer; Makse, Todd
Providing representation entails making choices about prioritizing the needs of diverse groups within one's constituency. While citizens cannot reasonably expect that representatives will cater to their particular interests or priorities all the time, we know little about citizens' expectations in this regard. In this paper, we present the results of two survey experiments that probe the relationship between citizens' group identifications, their perceptions of their constituencies, and their demands regarding representation. We find that citizens are generally egocentric, in that they expect a representative to cater to personally relevant interests even when such interests are not an important part of the representative's constituency. Moreover, we find that this egocentrism is not mitigated through the provision of information about the district's diversity or composition, indicating that voter ignorance about the nature of constituencies is not the primary cause of these expectations. Regardless of sophistication, we observe expectations that are unrealistically self-centered.